Electrical automation systems towards intelligent and energy efficiency applications - Mohamud Ahmed, Musse (IIUM Press, 2011)
Nowadays, intelligent distribution automation system is becoming important to the engineering industry in general and electrical engineering industry in particular. As electrical distribution system is one of the areas of electrical engineering in which automation system is very important to be implemented. This book contains three main parts. Part one of this book presents comprehensive automation application systems to electrical distribution industry and the equipment used. The typical distribution automation systems compose of master stations, equipment to be operated, controlled, and measured such as the distribution equipment for the electrical feeders, automating gasification plants, measuring their gas flows using sensors. It includes equipment at consumer side automation systems. It also includes control, monitoring, protection of the electrical distribution systems, remote metering of consumer loads, consumer side load management, energy efficiency assessment & optimization. In part two, the book covers communication and electronics automation areas which include: power line carriers or power lines applications, power line simulations, programmable gate arrays applications for light rail transit (LRT) systems, temperature and humidity control for public places using microcontrollers. Part three deals with energy efficiency issues for the electrical motors and air blowing equipment motors such as fans. It discusses and presents the best possible techniques of increasing the energy efficiency of the equipment used to save energy costs. This part consists of energy efficiency of the small scale most commonly used motors, motors for the fans and other similar motors. The book composes of thirty (35) chapters containing the three aforesaid parts.